Endovascular removal of intra-cardiac fractured port catheters due to pinch off syndrome: Report of 3 cases - Salih Çokpınar; Emir Hüseyin Nevai; Ahmet Tanyeri; Mustafa Gök (Radiology Case Reports)
Port catheters are widely used today due to increase in oncology cases, while they offer ease of use, they also bring various complications. These complications can range from simple issues to life-threatening ones. Port catheter fractures are rare complications, occurring in less than 1% of patients. The most common complaint in the present study was pain at the site of the subclavian vein puncture when fluid was administered from the port hub. Simple imaging such as chest X-rays can reveal the presence of the catheter fracture and migration. Pinch-off syndrome (POS) is one of the most significant causes of this condition. It is characterized by the catheter fracture compressed between the clavicle and the first rib. The incidence of POS ranges from 0.4% to 5%, with the clinical presentation varying widely from asymptomatic cases to serious complications such as cardiac arrhythmias, pulmonary embolism, or septic embolization. Early diagnosis is critical in preventing the life-threatening outcomes of POS. Diagnosis is usually made through imaging techniques such as chest X-rays, fluoroscopy, and thoracic computerized tomography (CT). Treatment of fracture due to POS typically involves the removal of catheter fragments using an endovascular technique, which offers lower morbidity compared to surgical methods. Prevention strategies include preferring internal jugular vein access over the subclavian vein, placing the subclavian entry point laterally, and performing regular imaging to detect POS symptoms early in the postprocedure period. This case series addresses case-based experiences where fractured port catheter fragments were successfully removed using endovascular methods also discussing the diagnostic and treatment process.